100th ANNIVERSARY – BIRTH OF ASSOCIATE PROFESSOR A.N. FRUMGARTS - Подолужный, Валерий Иванович; Павленко, Владимир Вячеславович; Радионов, Игорь Александрович (Medicine in Kuzbass, 2025)
The article presents the history of the formation and development of the famous Siberian surgeon, home front worker in the Great Patriotic War Abram Natanovich Frumgartz, Honored Doctor of the RSFSR